Pengaruh Promosi, Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Shegoo - Nawawi, Muhammad; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the influence of promotion, price, and service quality simultaneously and partially on Shegoo purchasing decisions. This study uses a quantitative method with stages of data collection through distributing questionnaires, analyzing data and testing hypotheses. The population in this study were students of UB, UM, UIN Malang who live in Malang City who have visited and made purchase transactions at SHEGOO. The sample used was students who had made Shegoo purchases. The number of samples used in this study was 72 respondents and was determined using the Malhota formula. The results of the study showed that promotion, price and service quality simultaneously had a significant effect on Purchasing Decisions. Promotion has a significant effect on Purchasing Decisions. Price has a significant effect on Purchasing Decisions. Service quality has a significant effect on Purchasing Decisions. Keywords : Promotion, Price, Service Quality And Purchasing Decisions